The Influence of Infographic Learning Media on Analytical Thinking Skills and Student Learning Outcomes - Ghinaa Ghaisani; Diana Hernawati; Egi Nuryadin (Bioedukasi: Jurnal Pendidikan Biologi, 2026)
The ability to think analytically is essential for students in the 21st century because it helps solve problems and make decisions. When students’ analytical thinking skills are low, it also affects their learning outcomes. One effort to improve this is through infographics. This study aims to determine the effect of infographic learning media on analytical thinking skills and student learning outcomes on the Genetic Substance material in class XII MIPA Madrasah Aliyah Negeri (MAN) 3 Tasikmalaya City. The research method used was a quasi-experimental design with a nonequivalent control group. The population in this study consisted of all XII MIPA MAN 3 Tasikmalaya City School Year 2023/2024, totaling 54 students. The sampling technique used was purposive sampling; class XII MIPA 2 was the experimental class, and class XII MIPA 1 was the control class. The instruments used were a multiple-choice test to measure learning outcomes (23 items) and a description test to measure analytical thinking skills (7 items). The data analysis technique used was ANCOVA. Based on the results of data analysis and hypothesis testing, the significance value for analytical thinking ability and learning outcomes is 0.000 (p ≤ 0.05). Therefore, it can be concluded that the infographic learning media has an effect on analytical thinking skills and student learning outcomes in the Genetic Substance material in class XII MIPA MAN 3 Tasikmalaya City.